2008
DOI: 10.1038/bmt.2008.375
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab markedly reduces chronic GVHD without affecting overall survival in reduced-intensity conditioning sibling allo-SCT for adults with AML

Abstract: By retrospective analysis of 88 patients from the British Society of Blood and Marrow Transplantation registry, we investigated the effect of in vivo T-cell depletion in HLA-identical sibling reduced-intensity conditioning (RIC) allografts for adult AML by comparing patients who received alemtuzumab with those without alemtuzumab conditioning. Both groups were equivalent for age, sex, karyotype and disease status at transplant. With a median follow-up of 27 months (3-72 months) and 48 months (7-72 months), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
2
27
0
2
Order By: Relevance
“…20 Malladi et al also observed higher infection risks and lower chronic GVHD in 51 patients who received alemtuzumab compared with 37 patients who did not. 21 We were unable to explore differences in cytomegalovirus reactivation between patients who received alemtuzumab and T cellreplete transplantations in the current analysis, but cytomegalovirus reactivation was not a more frequent cause of death in the alemtuzumab group. Unlike the current analysis, neither prior report observed differences in relapse.…”
Section: Discussionmentioning
confidence: 51%
“…20 Malladi et al also observed higher infection risks and lower chronic GVHD in 51 patients who received alemtuzumab compared with 37 patients who did not. 21 We were unable to explore differences in cytomegalovirus reactivation between patients who received alemtuzumab and T cellreplete transplantations in the current analysis, but cytomegalovirus reactivation was not a more frequent cause of death in the alemtuzumab group. Unlike the current analysis, neither prior report observed differences in relapse.…”
Section: Discussionmentioning
confidence: 51%
“…The use of alemtuzumab as a conditioning regimen was shown to be associated with reduced incidence of extensive chronic GVHD in the analysis of 88 patients receiving transplantation from an HLA-identical sibling graft [43]. However, the effect of alemtuzumab on the treatment of refractory chronic GVHD was reported only as a case report.…”
Section: Treatment Of Chronic Gvhdmentioning
confidence: 97%
“…One of the major areas of debate is the role of T cell depletion. T cell depletion in RIC HSCT has been shown to reduce the incidence of acute and chronic graft-versus-host disease (a/cGvHD) [2][3][4][5] but is associated with poorer disease control due to impairment of the graft-versus-leukaemia (GvL) effect [6]. The net outcome appears to be that overall survival is comparable between T-replete and T-depleted HSCT, with higher relapse-related deaths in T-depleted HSCT and higher transplant related mortality, including deaths from GvHD and its treatment, in T-replete HSCT [4,5].…”
Section: Introductionmentioning
confidence: 99%